Language Transfer in the Use of Pilipino - Roman, Jr, Guillermo Q. (Journal of Modern Languages, 2017)
This study attempts to identify the errors in the use of Pilipino by some Malaysian students and to find out the cause of the errors. In this paper the compositions written by eight students in Pilipino at the University of Malaya are analysed and the systematic errors are picked out. These are errors commenced by the learner based on the hypothesis formulated using his own internal grammar. These errors were then categorized as follows: omission, confusion, literal translation and wrong choice of words as in Duskova (1969), and Wong and Lim (1982).